Determination of HIV/AIDS Risk Behavioural Factors Among University of Dodoma Students in Tanzania (Tanzania Journal for Population studies and Development, 2011)
This study was conducted among university students at the University of Dodoma, and sought to determine whether knowledge on HIV/AIDS, attitudes and beliefs can predict practices that causes HIV infections. A pre-designed questionnaire was administered in this cross-sectional study in a sample of 547 (539 students plus 8 lecturers). The data on responses of students to HIV/AIDS related knowledge, attitudes and beliefs were analyzed preliminarily using frequencies and cross tabulations. Ordinal Logistic Regression (OLR) was used in analyzing the relationship between the dependent and independent variables. The OLR for sex under the influence of alcohol (p